Psychological Distress and Suicidal Behavior Among Medical Students at Khartoum State Universities, 2021-2022 - Mohamed Musa, Shima Algam; Mohamed, Abeer Mamoun; Osman, Sozan Mudather (International Journal of Medical Students, 2023)
Introduction: Psychological distress and suicidal behavior are mental health problems among students and necessitate research to inform strategies for prevention in this population. Although depressive symptoms and suicidal ideation are common in medical students, few programs address this problem, which is needed it to determine the prevalence of psychological distress and suicidal behavior among medical students. Methods: this is a cross sectional faculty-based study . we used Snowballing sampling technique and Kessler 10-item Questionnaire to assess psychological distress. We used SBQ-R (suicidal behavioral questionnaire _Revised) to assess suicidal behavior .The participants were students from 12 medical colleges in Khartoum state, from all academic levels. Results: among 525 undergraduate medical students 136 (25.9%) were males and 389 (74.1%) were females, 23.3% were well, 18.7% had mild mental disorder, 19.2%had moderate mental disorder and 38.8% had severe mental disorder at the last 30 days. The higher of psychological distress was slightly significant among student in preclinical years than clinical years (P=0.08), 72% have poor risk for suicidal ideation and 28% have higher risk of suicidal behavior more significant among students in preclinical years (p= 0.02). Conclusion: Psychological distress and suicidal behavior were more evident in pre-clinical years along with other many factor including, marital status, bad habits, chronic disease, and university type either public or private. We recommend implementing psychological and academic support programs across different undergraduate levels to enhance mental wellbeing, academic performance and prevent suicidal behavior.